The Fight against Smuggling at the Soviet-Polish Border throughout 1921-1939 - Roman Kotsan (Історико-політичні проблеми сучасного світу, 2017)
The article considers smuggling as economic crime in the Soviet-Polish border in the interwar period. The reasons for smuggling activities are studied and summarized. Range of smuggled goods is shown. The number of arrested smugglers, their nationality, the value of seized goods both from Poland and the Soviet Union are investigated. Smuggling as a political phenomenon in the Soviet-Polish border in 1921-1939 is under study. The use of smugglers by the intelligence agencies of both Poland and the USSR are emphasized. The role of public authorities of both abovementioned countries in the fight against smuggling, namely Border Guard Corps from Poland; border guards, customs, security services and local Soviet authorities on the part of the USSR are studied. The influence of anti smuggling measures (increased criminal liability, limitation of private capital in trade, strengthen of the state borders protection) on its amount decrease is studied.